Do "sinners" shift when the sin is taxed? a policy analysis of the 2012 Philippine Sin Tax on gambling expenditure across income deciles - Onsana, Angelica V.; Panti, Manica M.; Jandoc, Karl Robert (Quezon City School of Economics, University of the Philippines Diliman, 2023)
The Philippines ratified the Sin Tax Reform Law, or Republic Act 10351, in 2012, which aimed to increase the allocation of generated taxes directed to Department of Health’ (DOH) initiatives while decreasing rates of tobacco and alcohol consumption. In the Philippines, the sin tax is levied on the prices of tobacco goods and alcoholic beverages sold in the market. In other countries, gambling, or any game of chance activities, are also included in the said tax; however, this is not practiced in the Philippines. With this distinction, we hypothesize that an increase in the sin tax
declaration of the government would lead Filipinos to consume more of their income intended for vices to indulge instead in gambling. Results show that there is no fixed spending behavior that could embody the populace’s gambling decisions and that it is more dependent on the household’s disposable income. Although alcohol consumption decreased across all deciles, this did not imply that there had been a shift in gambling expenditure for all deciles as well. It is also observed that the majority of the lower-income deciles tend to decrease their consumption of gambling in contrast to higher-income earners.

While it is not possible to conclusively determine if allocations for vices immediately translate into increased gambling expenditure across deciles, it is essential to recognize the significance of policy reconsideration in light of the correlation between household income and gambling expenses. This provides an avenue for reframing, in light of recent discussions about reviewing the premises of the sin tax and what ‘sins’ should be included. The more justifiable identified ‘sins’ the government gets to recognize, the more accurate and clearer it will be to give a realistic projection of fund appropriation directed towards public health programs, all the while creating positive externalities from fostering a culture of healthier living.
Thesis (BS Economics) - - University of the Philippines Diliman
Keywords: Gambling -- Law and legislation -- Philippines; Gambling -- Taxation -- Philippines